Burnout while working lessons from pandemic and beyond - Cooper, Cary L.; Leiter, Michael P. (Current issues in work and organizational psychology, 2023)
"This book offers an extensive look into the ways living through the COVID-19 pandemic has deepened our understanding of the crises people experience in their relationships with work. Leading experts explore burnout as an occupational phenomenon that arises through mismatches between workplace and individuals on the day-to-day patterns in work life. A wide audience of students and researchers in psychology, management, business, healthcare, and social sciences, as well as policy makers in government and professional organizations, will benefit from this detailed insight into the ways COVID-19 has affected contemporary work attitudes and practices"--Provided by publisher.